Gender-Responsive product profile development tool. Workshop Report. November 12-13. Ithaca, USA - CGIAR Research Program on Roots, Tubers and Bananas; CGIAR Gender and Breeding Initiative (2018)
A small group of breeders, gender specialists and other breeding team members met for two days at Cornell University in Ithaca, NY in November of 2018 to review the first two prototype tools developed by the Gender in Breeding Initiative (GBI) and jointly work toward their refinement for the next steps of validation with case studies. These tools address the key questions of breeding for whom and prioritizing which traits with the Customer Profile and Product Profile Development Tools, respectively. GBI tools will be closely coordinated with the Product Design processes of the Excellence in Breeding Platform (EiB) of CGIAR, to assure gender relevance of tools for breeders in the CGIAR, as well as support to NARI and other programs.